If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = -5 + 6x + -2 Reorder the terms: 5 = -5 + -2 + 6x Combine like terms: -5 + -2 = -7 5 = -7 + 6x Solving 5 = -7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5 + -6x = -7 + 6x + -6x Combine like terms: 6x + -6x = 0 5 + -6x = -7 + 0 5 + -6x = -7 Add '-5' to each side of the equation. 5 + -5 + -6x = -7 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = -7 + -5 -6x = -7 + -5 Combine like terms: -7 + -5 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| 4U^2+8=-3u | | 5x-15=2x+4 | | n3=n/3 | | f(3)=64 | | -5(6y-5)-y=-4(y-4) | | 60x-12=14x^2-14x | | 9w=-9w^2-2 | | 4[y+1]-16=0 | | 9q^2-9q-54=0 | | 7=-2w^2+9w | | N=5st^4-2sx | | 7r^2=-3r | | 5z^2=-4z | | 3w+7=21 | | 14=5b | | f-x=-x^2+9(-x)-3 | | 6=-5r^2 | | -9=-8s^2 | | 12x+9(2x+5)= | | 4W^2+4w=-5 | | 2=-9v^2+6v | | 8y+8=5y-4 | | 7T^2=-6 | | 2(3a+2a*6a-4a)=7a+5 | | C=(5/9)(F=32) | | C=5/9(F=32) | | 9a-15=57 | | 4x^2-3=61 | | 744*x=5.84 | | g(x)=2x^2-5x-1 | | 6*2-(-6)= | | z=-2/2 |